Self-supporting porous nitrogen-doped graphene network lithium metal main material and preparation method
Through the preparation of lithium metal main material of self-supporting porous nitrogen-doped graphene network, the problems of dendrites growth and volume expansion of lithium metal batteries during circulation are solved, the rate performance and Coulomb efficiency are improved, and the effect of fast charging and discharging is achieved. .
Patent Information
- Application Number
- CN202211040199.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-08-29
AI Technical Summary
Existing lithium metal batteries have dendrite growth and volume expansion problems during the circulation process, resulting in poor Coulombic efficiency and circulation performance, and it is difficult to achieve rapid charging and discharge.
The self-supported porous nitrogen-doped graphene network lithium metal main material is prepared through two steps: self-assembly of liquid-gas interface and high-temperature annealing to achieve the porous structure and high lithium-philicity of the material.
It improves the rate performance and Coulomb efficiency of lithium metal batteries, reduces the uneven deposition of lithium ions, alleviates the volume expansion of the lithium metal anode during the circulation, and realizes the need for fast charging and discharging.
Smart Images

Figure CN115241445B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a self-supporting porous nitrogen-doped graphene network lithium metal main body material and a preparation method thereof. Background Art
[0002] Lithium metal is considered an important anode for next-generation high-energy-density batteries due to its high theoretical specific capacity, lowest negative electrochemical potential, and light weight. However, the dendrite growth and volume expansion of lithium metal are huge challenges that seriously hinder its practical application. In order to commercialize lithium metal anodes, considerable efforts have been invested in introducing lithium metal host materials to inhibit the dendrite growth and volume expansion of lithium metal during cycling, thereby improving the coulombic efficiency and cycling performance of lithium metal batteries. Generally, an ideal lithium metal host material requires excellent conductivity, high specific surface area, and outstanding electrochemical stability. To this end, graphene films represent the most attractive class of lithium metal host materials.
[0003] Graphene films have attracted great attention due to their good electrical conductivity and excellent mechanical flexibility. However, due to the strong π-π interaction between graphene sheets, graphene sheets tend to agglomerate, which seriously reduces the contact area with the electrolyte, resulting in poor Coulombic efficiency and cycling performance.
[0004] Studies have shown that designing nanostructures in graphene-based host materials can inhibit the aggregation of graphene sheets and increase the interface contact area, thereby improving the coulombic efficiency and cycle performance of the battery. The Chinese patent application number 201811392954.6 discloses a self-supporting composite three-dimensional composite lithium metal anode, which is prepared by mixing zinc fluoride, magnesium fluoride and graphene oxide solution evenly, then filtering and drying to obtain a composite graphene film, and finally preparing a graphene-based composite lithium metal anode by melt-filling lithium. To a certain extent, the cycle stability of the battery is improved, but it cannot solve the problem of poor rate of lithium metal batteries, and cannot meet the demand for rapid charging and discharging of batteries. In addition, the preparation process is cumbersome and complicated, and it is difficult to prepare on a large scale. Summary of the invention
[0005] In view of the technical problems existing in the prior art, the present invention provides a self-supporting porous nitrogen-doped graphene network lithium metal main material and a preparation method, so as to achieve the high rate performance of lithium metal batteries, promote the development of lithium metal batteries, and provide a new self-supporting lithium metal main material for fast charging and discharging. The operation is simple and can be prepared on a large scale.
[0006] The technical solution adopted by the present invention is: a method for preparing a self-supporting porous nitrogen-doped graphene network lithium metal main material, comprising the following steps:
[0007] Step 1: dispersing graphene oxide in deionized water, and ultrasonically dispersing to form a suspension to obtain a graphene oxide suspension;
[0008] Step 2: adding vat red F3B dye to the suspension obtained in step 1, ultrasonicating and stirring to obtain a mixed solution;
[0009] Step 3: pour the mixed solution of step 2 into the template, put it into an oven to form a film through liquid-gas interface self-assembly, the temperature is 35-90°C, and a self-supporting composite film is obtained;
[0010] Step 4: heat-treat the composite film of step 3 under a protective atmosphere at a temperature of 300 to 1000°C, a time of 0.5 to 5 hours, and a heating rate of 1 to 15°C / min to obtain a self-supporting porous nitrogen-doped graphene network lithium metal main material.
[0011] Furthermore, the mass ratio of graphene oxide to vat red F3B dye is 1:0.2-1.
[0012] Furthermore, the template is a polytetrafluoroethylene template.
[0013] The technical solution adopted by the present invention is: the self-supporting porous nitrogen-doped graphene network lithium metal main material prepared by the above preparation method.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] 1. The present invention prepares a self-supporting porous nitrogen-doped graphene network lithium metal main material through two steps of liquid-gas interface self-assembly and high-temperature annealing. Compared with the existing method for preparing nitrogen-doped graphene, it does not need to prepare a variety of solutions and does not require cumbersome multi-step reactions. It is easy to operate and has good controllability. Therefore, large-scale preparation can be achieved.
[0016] 2. The present invention adopts vat red F3B dye as a nitrogen source. Vat red F3B dye is commonly used in industrial cotton fiber dyeing and cotton cloth printing. It is cheap and abundant in source, and has very good practical prospects. Different from commonly used nitrogen sources such as ammonia water, urea and melamine, it can provide a nitrogen source and obtain porous nitrogen-doped graphite carbon through a high-temperature carbonization process, which can improve the structural stability of nitrogen-doped graphene.
[0017] 3. The self-supporting porous nitrogen-doped graphene network lithium metal main material prepared by the present invention has abundant nanopores in the porous nitrogen-doped graphene network that can serve as a shortcut path for ion diffusion between different layers of graphene, thereby accelerating the transmission of ions in the entire film, greatly improving the rate performance of the battery; nitrogen-doped graphene has a stronger force on lithium ions, making the lithium metal main material have better lithium affinity, which can effectively reduce the nucleation overpotential and guide the uniform deposition of lithium; the porous graphene network has a large specific surface area, which can even out the space charge and reduce the local current density, thereby avoiding the uneven deposition of lithium ions, and thus ensuring high coulombic efficiency. The porous lithium metal main material can provide good mechanical stability and open pores, effectively alleviate the volume expansion of the lithium metal anode during the cycle, and improve the stability of the electrode size. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a flow chart of an embodiment of the present invention;
[0019] Figure 2 This is the XPS spectrum of the self-supporting porous nitrogen-doped graphene network lithium metal main material of Example 1 of the present invention;
[0020] Figure 3 This is a scanning electron microscope image of the self-supporting porous nitrogen-doped graphene network lithium metal main material of Example 1 of the present invention;
[0021] Figure 4 It is a rate performance diagram of Example 1 of the present invention and the comparative example in a symmetrical battery;
[0022] Figure 5 This is a rate performance diagram of Example 1 of the present invention and a comparative example in a lithium-sulfur battery;
[0023] Figure 6 This is a scanning electron microscope image of the self-supporting porous nitrogen-doped graphene network lithium metal main material of Example 2 of the present invention;
[0024] Figure 7 It is a rate performance diagram of Example 2 of the present invention and the comparative example in a symmetrical battery;
[0025] Figure 8 This is a rate performance diagram of Example 2 of the present invention and a comparative example in a lithium-sulfur battery;
[0026] Fig. 9 This is a scanning electron microscope image of the self-supporting porous nitrogen-doped graphene network lithium metal main material of Example 3 of the present invention;
[0027] Fig.10 It is a rate performance diagram of Example 3 of the present invention and the comparative example in a symmetrical battery;
[0028] Fig.11This is a rate performance diagram of Example 3 of the present invention and the comparative example in a lithium-sulfur battery. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0030] Example 1
[0031] The embodiment of the present invention provides a method for preparing a self-supporting porous nitrogen-doped graphene network lithium metal main material, such as Figure 1 As shown, it includes the following steps:
[0032] Step 1: Using graphite as raw material, graphene oxide was prepared by freeze drying using a modified Hummers method. 170 mg of graphene oxide was weighed and ultrasonically treated in 35 mL of deionized water for 1 h to obtain a graphene oxide suspension.
[0033] Step 2: 170 mg of vat red F3B dye was slowly added to the above suspension, magnetically stirred for 20 min, and ultrasonically treated for 20 min. This was repeated three times to obtain a mixed solution.
[0034] Step 3: Pour the above solution into a 10 cm×10 cm polytetrafluoroethylene template, and then put it into an oven at 90° C. to dry for 2 h, and obtain a self-supporting composite film through liquid-gas interface self-assembly.
[0035] Step 4: Use a punching machine to punch the composite film into a circular electrode with a diameter of 12 mm, put the above-mentioned electrode into a tubular furnace, and heat treat it at 1000°C for 0.5 h at a heating rate of 15°C / min in an argon atmosphere. After cooling to room temperature, a self-supporting porous nitrogen-doped graphene network lithium metal main material is obtained.
[0036] Figure 2 This is the XPS spectrum of the self-supporting porous nitrogen-doped graphene network lithium metal main material of Example 1 of the present invention. It can be seen from the figure that the peaks at 284.67, 285.37, 286.57 and 288.27 eV in the C 1s spectrum belong to CC, CN, COC, C=O, respectively, and the peaks at 398.11 and 399.36 eV in the N 1s spectrum are pyrrolic nitrogen and pyridinic nitrogen, respectively, proving the successful introduction of nitrogen atoms. Since pyridinic nitrogen and pyrrolic nitrogen have a stronger force on lithium ions, the lithium metal main material has better lithium affinity, can effectively reduce the nucleation overpotential, guide the uniform deposition of lithium, and thus improve the electrochemical performance.
[0037] Figure 3This is a scanning electron microscope (SEM) image of the self-supporting porous nitrogen-doped graphene network lithium metal main material of invention embodiment 1. From the image, it can be seen that the surface has abundant nanopores, which can serve as a shortcut path for ion diffusion between different graphene layers, thereby accelerating the transmission of ions in the entire film and greatly improving the battery's rate performance.
[0038] In order to evaluate the electrochemical performance of the composite anode with a self-supporting porous nitrogen-doped graphene network as the lithium metal main material, the material prepared in Example 1 was verified as follows:
[0039] The self-supporting porous nitrogen-doped graphene network lithium metal main material prepared in Example 1 was used as the working electrode, and lithium foil was used as the counter electrode and reference electrode. The assembled battery was charged at 0.5 mA cm -2 The current density of 5 mAh cm-2 on the free-standing porous nitrogen-doped graphene network pre-deposited with lithium metal host material -2 Lithium metal, to obtain a composite anode with a self-supporting porous nitrogen-doped graphene network as the lithium metal main material.
[0040] Symmetrical batteries were assembled using composite anodes and their rate performance at different current densities was tested.
[0041] Figure 4 1 is a rate performance diagram of Example 1 of the present invention and the comparative example in a symmetrical battery. As can be seen from the figure, compared with the comparative example, Example 1 exhibits lower hysteresis voltage at different current densities, even at a current density of 5 mA cm -2 , the cycle capacity is 5 mAh cm -2 Under the cycling conditions, the hysteresis voltage is only 64 mV, showing excellent rate performance.
[0042] The composite anode is matched with the sulfur positive electrode to be assembled into a lithium-sulfur battery, and its rate performance at different current densities is tested.
[0043] Figure 5 The figure shows the rate performance of Example 1 and the comparative example in a lithium-sulfur battery. As shown in the figure, compared with the comparative example, Example 1 shows higher capacity at different rates. Even at a rate of 3C, its cycle capacity is still as high as 437 mAh g -1 , showing excellent rate performance.
[0044] Example 2
[0045] The embodiment of the present invention provides a method for preparing a self-supporting porous nitrogen-doped graphene network lithium metal main material, such as Figure 1 As shown, it includes the following steps:
[0046] Step 1: Using graphite as raw material, graphene oxide was prepared by freeze drying using a modified Hummers method. 170 mg of graphene oxide was weighed and ultrasonically treated in 35 mL of deionized water for 1 h to obtain a graphene oxide suspension.
[0047] Step 2: 85 mg of vat red F3B dye was slowly added to the above suspension, magnetically stirred for 20 min, and ultrasonically treated for 20 min. This was repeated three times to obtain a mixed solution.
[0048] Step 3: Pour the above solution into a 10 cm×10 cm polytetrafluoroethylene template, and then put it into an oven at 60° C. to dry for 3 h, and obtain a self-supporting composite film through liquid-gas interface self-assembly.
[0049] Step 4: Use a punching machine to punch the composite film into a circular electrode with a diameter of 12 mm, put the above-mentioned electrode into a tubular furnace, and heat treat it at 700°C for 2 hours at a heating rate of 8°C / min in an argon atmosphere. After cooling to room temperature, a self-supporting porous nitrogen-doped graphene network lithium metal main material is obtained.
[0050] Figure 6 This is a scanning electron microscope (SEM) image of the self-supporting porous nitrogen-doped graphene network lithium metal main material of invention embodiment 2. From the image, it can be seen that the surface has abundant nanopores, which can serve as a shortcut path for ion diffusion between different graphene layers, thereby accelerating the transmission of ions in the entire film and greatly improving the battery's rate performance.
[0051] In order to evaluate the electrochemical performance of the composite anode with a self-supporting porous nitrogen-doped graphene network as the lithium metal main material, the material prepared in Example 2 was verified as follows:
[0052] The self-supporting porous nitrogen-doped graphene network lithium metal main material prepared in Example 2 was used as the working electrode, and lithium foil was used as the counter electrode and reference electrode. The assembled battery was charged at 0.5 mA cm -2 The current density of 5 mAh cm-2 on the free-standing porous nitrogen-doped graphene network pre-deposited with lithium metal host material -2 Lithium metal, to obtain a composite anode with a self-supporting porous nitrogen-doped graphene network as the lithium metal main material.
[0053] Symmetrical batteries were assembled using composite anodes and their rate performance at different current densities was tested.
[0054] Figure 7 2 is a rate performance diagram of Example 2 of the present invention and the comparative example in a symmetrical battery. As can be seen from the figure, compared with the comparative example, Example 2 exhibits lower hysteresis voltage at different current densities, even at a current density of 5 mA cm -2, the cycle capacity is 5 mAh cm -2 Under the cycling conditions, the hysteresis voltage is only 65mV, showing excellent rate performance.
[0055] The composite anode is matched with the sulfur positive electrode to be assembled into a lithium-sulfur battery, and its rate performance at different current densities is tested.
[0056] Figure 8 The figure shows the rate performance of Example 2 and the comparative example in a lithium-sulfur battery. As shown in the figure, compared with the comparative example, Example 2 shows higher capacity at different rates. Even at a rate of 3C, its cycle capacity is still as high as 455 mAh g -1 , showing excellent rate performance.
[0057] Example 3
[0058] The embodiment of the present invention provides a method for preparing a self-supporting porous nitrogen-doped graphene network lithium metal main material, such as Figure 1 As shown, it includes the following steps:
[0059] Step 1: Using graphite as raw material, graphene oxide was prepared by freeze drying using a modified Hummers method. 170 mg of graphene oxide was weighed and ultrasonically treated in 35 mL of deionized water for 1 h to obtain a graphene oxide suspension.
[0060] Step 2: 38 mg of vat red F3B dye was slowly added to the above suspension, magnetically stirred for 20 min, and ultrasonically treated for 20 min. This was repeated three times to obtain a mixed solution.
[0061] Step 3: Pour the above solution into a 10 cm×10 cm polytetrafluoroethylene template, and then put it into an oven at 35° C. to dry for 8 h, and obtain a self-supporting composite film through liquid-gas interface self-assembly.
[0062] Step 4: Use a punching machine to punch the composite film into a circular electrode with a diameter of 12 mm, put the above-mentioned electrode into a tubular furnace, and heat treat it at 300°C for 5 hours at a heating rate of 1°C / min in an argon atmosphere. After cooling to room temperature, a self-supporting porous nitrogen-doped graphene network lithium metal main material is obtained.
[0063] Fig. 9 This is a scanning electron microscope (SEM) image of the self-supporting porous nitrogen-doped graphene network lithium metal main material of invention embodiment 3. From the image, it can be seen that the surface has abundant nanopores, which can serve as a shortcut path for ion diffusion between different graphene layers, thereby accelerating the transmission of ions in the entire film and greatly improving the battery's rate performance.
[0064] In order to evaluate the electrochemical performance of the composite anode with a self-supporting porous nitrogen-doped graphene network as the lithium metal main material, the material prepared in Example 3 was verified as follows:
[0065] The self-supporting porous nitrogen-doped graphene network lithium metal main material prepared in Example 3 was used as the working electrode, and lithium foil was used as the counter electrode and reference electrode. The assembled battery was charged at 0.5 mA cm -2 The current density of 5 mAh cm-2 on the free-standing porous nitrogen-doped graphene network pre-deposited with lithium metal host material -2 Lithium metal, to obtain a composite anode with a self-supporting porous nitrogen-doped graphene network as the lithium metal main material.
[0066] Symmetrical batteries were assembled using composite anodes and their rate performance at different current densities was tested.
[0067] Fig.10 3 is a rate performance diagram of Example 3 of the present invention and the comparative example in a symmetrical battery. As can be seen from the figure, compared with the comparative example, Example 3 exhibits lower hysteresis voltage at different current densities, even at a current density of 5 mA cm -2 , the cycle capacity is 5 mAh cm -2 Under the cycling conditions, the hysteresis voltage is only 50mV, showing excellent rate performance.
[0068] The composite anode is matched with the sulfur positive electrode to be assembled into a lithium-sulfur battery, and its rate performance at different current densities is tested.
[0069] Fig.11 The figure shows the rate performance of Example 3 of the present invention and the comparative example in a lithium-sulfur battery. As shown in the figure, compared with the comparative example, Example 3 shows higher capacity at different rates. Even at a rate of 3C, its cycle capacity is still as high as 417 mAh g -1 , showing excellent rate performance.
[0070] Comparative Example
[0071] The preparation method of reduced graphene oxide lithium metal main material and composite anode, symmetrical battery and lithium sulfur battery comprises the following steps:
[0072] Step 1: Using graphite as raw material, graphene oxide was prepared by freeze drying using a modified Hummers method. 170 mg of graphene oxide was weighed and ultrasonically treated in 35 mL of deionized water for 1 h to obtain a suspension.
[0073] Step 2: Pour the obtained suspension into a 10cm×10cm polytetrafluoroethylene template, put it into a 60℃ oven for drying for 3h, and obtain a self-supporting composite film through liquid-gas interface self-assembly, and use a punching machine to punch out a circular electrode with a diameter of 12mm. Put the above-mentioned electrode into a tube furnace, heat treat it at 700℃ for 2h at a heating rate of 8℃ in an argon atmosphere, and cool it to room temperature to obtain the reduced graphene oxide lithium metal main material.
[0074] Step 3: The reduced graphene oxide lithium metal host material of step 2 was used as the working electrode, and lithium foil was used as the counter electrode and reference electrode. The assembled battery was charged at 0.5 mA cm -2 The current density in the reduced graphene oxide pre-deposited lithium metal host material is 5 mAh cm -2 Lithium metal is obtained to obtain a composite anode with reduced graphene oxide as the lithium metal main material.
[0075] Step 4: Assemble the composite anode obtained in step 3 into a symmetrical battery and test its rate performance at different current densities.
[0076] Step 5: Match the composite anode obtained in step 3 with the sulfur positive electrode to assemble a lithium-sulfur battery, and test its rate performance at different current densities.
[0077] The present invention has been described in detail above through embodiments, but the contents described are only exemplary embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. The protection scope of the present invention is defined by the claims. Anyone who utilizes the technical solution described in the present invention, or a technician in the field, inspired by the technical solution of the present invention, designs a similar technical solution within the essence and protection scope of the present invention to achieve the above technical effects, or makes equal changes and improvements to the scope of application, etc., shall still fall within the scope of protection covered by the patent of the present invention.
Claims
1. A method for preparing a self-supporting porous nitrogen-doped graphene network lithium metal main material, characterized in that: The following steps are involved: Step 1: dispersing graphene oxide in deionized water, and ultrasonically dispersing to form a suspension to obtain a graphene oxide suspension; Step 2: adding vat red F3B dye to the suspension obtained in step 1, ultrasonicating and stirring to obtain a mixed solution; Step 3: Pour the mixed solution of step 2 into the template, put it into an oven to form a film through liquid-gas interface self-assembly at a temperature of 35-90°C, and obtain a self-supporting composite film; Step 4: heat-treating the composite film of step 3 under a protective atmosphere, the heat treatment temperature is 300-1000°C, the heat treatment time is 0.5-5 h, and the heating rate is 1-15°C / min to obtain a self-supporting porous nitrogen-doped graphene network lithium metal main material; The mass ratio of graphene oxide to vat red F3B dye is 1:0.2-1; The template is a polytetrafluoroethylene template.
2. The self-supporting porous nitrogen-doped graphene network lithium metal main material prepared by the preparation method of the self-supporting porous nitrogen-doped graphene network lithium metal main material in claim 1.
Citation Information
Patent Citations
Graphene-based high-performance composite lithium metal negative electrode material and preparation method thereof
CN109841797A
KR20220018131A